Is subcutaneous adipose tissue expansion in people living with lipedema healthier and reflected by circulating parameters? - Nankam, Pamela A. Nono; Cornely, Manuel; Klöting, Nora; Blüher, Matthias (Frontiers in Endocrinology, 2022)
Lipedema may be considered a model for healthy expandability of subcutaneous adipose tissue (SAT). This condition is characterized by the disproportional and symmetrical SAT accumulation in the lower-body parts and extremities, avoiding the abdominal area. There are no circulating biomarkers facilitating the diagnosis of lipedema. We tested the hypothesis that women living with lipedema present a distinct pattern of circulating parameters compared to age- and BMI-matched women. In 26 women (Age 48.3±13.9 years, BMI 32.6±5.8 kg/m2; lipedema group: n=13; control group: n=13), we assessed circulating parameters of glucose and lipid metabolism, inflammation, oxidative stress, sex hormones and a proteomics panel. We find that women with lipedema have better glucose metabolism regulation represented by lower HbA1c (5.55 ± 0.62%) compared to controls (6.73 ± 0.85%; p<0.001); and higher adiponectin levels (lipedema: 4.69 ± 1.99 mmol/l; control: 3.28 ± 1.00 mmol/l; p=0.038). Despite normal glycemic parameters, women with lipedema have significantly higher levels of total cholesterol (5.84 ± 0.70 mmol/L vs 4.55 ± 0.77 mmol/L in control ; p<0.001), LDL-C (3.38 ± 0.68 mmol/L vs 2.38 ± 0.66 mmol/L in control; p=0.002), as well as higher circulating inflammation (top 6 based on p-values: TNFSF14, CASP8, EN-RAGE, EIF4EBP1, ADA, MCP-1) and oxidative stress markers (malondialdehyde, superoxide dismutase and catalase). Our findings suggest that the expected association between activation of inflammatory and oxidative stress pathways and impaired glucose metabolism are counterbalanced by protective factors in lipedema.